Investigating the microwave properties of carbon materials from microwave-driven methane pyrolysis - Sama Manzoor; Omar Bashir Wani; Erin R. Bobicki (Carbon Trends, 2024)
Rising carbon dioxide emissions due to fossil fuel combustion has led to the urgent need to investigate and adopt different energy solutions that can mitigate this problem. Hydrogen has surfaced as a promising alternative in the pursuit for CO2-neutral energy systems. Microwave pyrolysis of methane has recently emerged as an innovative method to accomplish this goal. To enhance our understanding of this technique and its scalability, it is essential to explore the microwave characteristics of the carbon used and generated during this process. This work investigates the microwave properties of two carbon samples (seed carbon; SC and product carbon; PC) from microwave-driven pyrolysis of methane. The cavity perturbation technique was employed from room temperature to 1250 °C for frequencies of 397, 912, 1429, 1948 and 2467 MHz. Thermogravimetric analysis (TGA), differential scanning calorimetry (DSC) and X-ray diffraction (XRD) analysis were also performed to elucidate the permittivity results. It was found that SC initially showed a decline in permittivity values up to 200 °C which is attributed to the release of moisture from the sample. These results were correlated to TGA/DSC which showed 5 % mass loss from 100 to 155 °C. The permittivity gradually reached a peak after which it started to fall due to high conductivity. In the case of the PC, the permittivities exhibited undulations but the values remained consistent. Since this form of carbon is formed at elevated temperature, no loss in moisture was seen in TGA/DSC. These findings indicate that the microwaves can penetrate and heat both the samples uniformly across their entire volume, resulting in efficient heating. SC demonstrated higher permittivity magnitudes compared to PC, suggesting its better responsiveness to microwave fields. Nonetheless, the possibility of thermal runaway in SC renders it less favorable for applications involving microwave-driven pyrolysis. XRD analysis showed that the samples SC and PC demonstrated amorphous carbon structures, with PC showing indications of graphitization to some extent. Both SC and PC have the potential to serve as microwave heat carriers in the methane pyrolysis process. This suggests that utilizing the carbon produced can enable a self-sufficient process, eliminating the necessity for costly catalysts.